PEMBERIAN KUASA LISAN UNTUK MEWAKILI PEMEGANG SAHAM DALAM RAPAT UMUM PEMEGANG SAHAM - Darmawati, Darmawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Power of attorney establishment accomodates and helps someone who is hindered to execute their rights and obligations directly. Those limitations can be solved by giving a power of attorney to other people as an endorsee. Giving a power of attorney can be done in writing or verbally. To proof a power of attorney which was given verbally is actually very difficult. Considering that a power of attorney by verbal is simpler, there is a lot of people who is doing so, with no exception is shareholders in a limited company who give a power of attorney verbally to someone to represent them in a General Meeting of Shareholder. An endorsee who receives a power of attorney verbally from shareholders, which is difficult to proof, will represent shareholders' voting rights in a General Meeting of Shareholder to fulfill meeting quorum and give voting rights in shareholders decision making.